Multifunctional MgAl LDH/Zn-MOF S-scheme heterojunction - Maseeh, Ihsan (2024)
Funding Information: M. B. T. acknowledges support from HEC (Higher Education Commission) of Pakistan and thanks Dr Muhammad Imran (QAU) for help in the H evolution activity. A. A. acknowledges support from King Abdulaziz University, P. O. Box 42734, Jeddah, Saudi Arabia. S. A. C. C. acknowledges support from FCT/MCTES, Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior, DOIs: 10.54499/LA/P/0008/2020, 10.54499/UIDP/50006/2020, 10.54499/UIDB/50006/2020 and the Scientific Employment Stimulus \u2013 Institutional Call (DOI: 10.54499/CEECINST/00102/2018/CP1567/CT0026). Publisher Copyright: © 2024 RSC.